The Effect of 8 Weeks Resistance Training With Low Load and High Load on Testosterone, Insulin-like Growth Factor-1, Insulin-like Growth Factor Binding Protein-3 Levels, and Functional Adaptations in Older Women - Esmat Rashidi; Seyed Ali Reza Hosseini Kakhak; Roya Askari (University of Social Welfare & Rehabilitation Sciences, 2019)
Objectives The loss of muscle mass in older adults is attributed to the impaired ability of the skeletal muscle in response to anabolic stimuli and the increased activation of the proteolytic signaling pathway. With increasing age, plasma concentrations of circulating anabolic hormones and growth factors, e.g. testosterone, Insulin-like Growth Factor-1 (IGF-1) and Insulin-like Growth Factor Binding Protein-3 (IGFBP-3) are also diminished. Resistance Training (RT) promotes positive adaptations that attenuate the harmful effects of aging. The aim of this investigation was evaluation the impact of RT with Low Load (LL) and high load (HL) on the testosterone, IGF-1, IGFBP-3 levels and functional adaptations in older women. Methods & Materials A total of 28 older women (Mean±SD age: 63.14±2.51 y) eligible to participate in this study were randomly assigned into three groups of RT with Low Load (RT-LL) (30٪ 1RM [one repetition maximum test]), RT group with High Load (RT-HL) (80٪ 1RM) and control group. Both training groups performed the exercise until fatigue. The minimum number of repetitions for the RT-LL group was 20 and for the RT-HL group 8. The RT program was executed three sessions per week for 8 weeks. Testosterone, IGF-1, IGFBP-3, lower body muscular strength, and muscular endurance of the subjects were measured before and after the intervention. Results No significant changes were observed in testosterone, IGF-1, and IGFBP-3 levels after 8 weeks of RT (P>0.05). Both training groups significantly increased the lower body muscular strength and muscular endurance (P<0.05), and there was no significant difference between the two RT groups (P>0.05). Conclusion Based on the study findings, RT-LL until the fatigue may affect performance adaptations resulting from exercise and provide an appropriate alternative to RT-HL in older people.